Fasting cancer : how fasting and nutritechnology are creating a revolution in cancer prevention and treatment - Longo, Valter, 1967- (Avery, an imprint of Penguin Random House, 2025)
"A groundbreaking guide to how fasting and nutritechnology are revolutionizing the prevention and treatment of cancer, from the bestselling author of The Longevity Diet"--